Impact of Sars-CoV-2 prophylaxis with tixagevimab-cilgavimab in high-risk patients with B-cell malignancies: a single-center retrospective study. - Giovanni Manfredi Assanto ,; Matteo Totaro; Poggiali Rebecca; Delli Paoli Adele; Annechini Giorgia; D’Elia Gianna Maria; Aji Francesco; Petrucci Luigi; Fazio Francesca; Del Giudice Ilaria; Martelli Maurizio; Micozzi Alessandra; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Severe Acute Respiratory Syndrome CoronaVirus‐2 (SARS‐CoV‐2) infection can result in different clinical manifestations (COVID-19), starting from asymptomatic disease to life threatening respiratory insufficiency. Onco-haematologic patients are at higher risk to develop severe COVID-19. In particular, patients affected by lymphoproliferative diseases, given the impaired cell-mediated and antibody-mediated immunity and treatment toxicity, develop more often a symptomatic and a more serious disease of Covid-19. Various therapeutic and prophylactic agents are being used against COVID‐19 such as antiviral drugs, vaccines and antiviral S‐protein monoclonal antibodies. Pre-exposure prophylaxis with AZD442/Evusheld (tixagevimab-cilgavimab) may be a complementary strategy to decrease the incidence or severity of COVID-19 for patients with B-cell malignancies. Tixagevimab-cilgavimab is a combination of two monoclonal antibodies that bind SARS-CoV-2 spike protein and inhibits the attachment to the surface of cells, preventing viral entry in the cell and COVID-19 development. In the setting of hematology real-life, few data are available on the impact of pre-exposure prophylaxis, given the multiple factors involved in the clinical behavior of SARS-CoV-2 . Our aim was to evaluate the clinical benefit and the safety of this strategy at our center.